Pre-service management teachers’ preparedness in adapting curriculum for an inclusive classroom - Afful, Henry Abeiku (University of Cape Coast, 2023)
The research examined pre-service management teachers’ preparedness in adapting the curriculum for an inclusive classroom. The study used the concurrent embedded mixed-methods research design. Through census survey, 164 respondents were studied in the quantitative phase of the study and the purposive sample of lecturers (n = 7) and 20 trainee-teachers partook the followup qualitative aspect. Questionnaires and interview guides were used to gather data from participants. Descriptive and inferential statistics were used to analyse the quantitative data, and thematic analysis for the qualitative data. The study established that pre-service management teachers had a moderate level of knowledge of inclusive classroom practices (KICP). They were highly prepared to use classroom management strategies (CMS) and time management strategies (TMS) but moderately prepared to use differentiated instruction strategies (DIS) in an inclusive classroom. The implementation of the “Special Education Course” and other professional courses that infuse inclusivity supports pre-service management teachers’ preparation for an inclusive classroom. However, pre-service management teachers felt they were not ready for inclusive classrooms because they had student concerns, personal concerns, management concerns, facilities, and environmental concerns. Gender and age of pre-service management teachers had a significant influence on inclusive classroom instructional strategies (DIS, CMS and TMS). Significant gender differences were found in pre-service management teachers’ use of TMS. However, there was no statistically significant difference in pre-service management teachers’ KICP, DIS and CMS based on gender and prior teaching experience. Pre-service management teachers’ KICP significantly influenced their preparedness for using inclusive classroom instructional strategies (DIS, CMS and TMS). Pre-service management teachers must be given more inclusive education knowledge through in-service training and practical experiences to enhance their classroom practices. Management education programmes should focus on diverse instructional strategies, particularly DIS, CMS, and TMS, while addressing potential gender-related disparities in TMS use. Management education programmes should emphasize knowledge enhancement, attitude shifts, and sustained support for teachers in inclusive education. Pre-service management teachers need to be supported with sufficient resources and learning support providers to effectively implement SEND strategies in their classrooms.
xiv, 241p :,ill
Keywords: Classroom management strategies Differentiated instruction strategies. Knowledge of Inclusive Classroom Practices Inclusive education Pre-service management teachers Time management strategies